Analisis Penerapan Pajak Pertambahan Nilai (PPN) Atas Transaksi E-Commerce Pada Platform Shopee (Studi Kasus Merchant Kalibre Di Kota Medan) - Beniati Gea; Dwi Saraswati (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The rapid growth of e-commerce in Indonesia has encouraged the government to optimize tax revenue, particularly Value Added Tax (VAT) on Electronic Commerce Transactions (PMSE). This study aims to analyze the implementation of VAT on e-commerce transactions on the Shopee platform, specifically focusing on Kalibre Merchants in Medan City, and to examine the impact of VAT implementation on the merchant. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving informants from Shopee Indonesia, PT Kalibre Indonesia, and the Regional Office of the Directorate General of Taxes in North Sumatra. The results indicate that the implementation of VAT on e-commerce transactions on the Shopee platform has been carried out in accordance with the Regulation of the Minister of Finance Number 60/PMK.03/2022, in which Shopee is designated as a VAT collector for PMSE transactions. VAT is automatically collected at the time of transaction and remitted to the government by the platform. However, differences in understanding regarding service fees and VAT components were found among consumers and merchants. The implementation of VAT has administrative implications for Kalibre Merchants but does not significantly affect sales volume, as the VAT collection mechanism is fully integrated into the platform system. This study is expected to contribute to improving tax awareness and compliance in the e-commerce sector.